Essential Attributes of the Accounting Information in Applying the Financial Reporting Differences Between IFRS and US GAAP - Herbei (Mot), Ioana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
In the context of the development of information, the main role of financial reporting is threatened by alternative sources of information that users use. However, the main source of information for decision-makers remain the accounting information relaxed from synthesis financial reporting, because the legal framework prescribes mandatory minimum information and a set of quality certification mechanisms thereof. As a starting point in our research we used relevant studies from the scientific literature regarding the understanding of the accounting information in financial reporting. We specify that many authors place the accounting information in the perimeter of the objectivity and the accuracy, which is essential in making economic decisions by the leadership. Thus, in support of decisionmakers, accountants apply professional judgment (judgment of International Financial Reporting Standards), taking decisions in terms of the use of accounting treatments to achieve a quality of financial reporting information. The contents of the article have been reported not only attributes on accounting information provided by IFRS, but also aspects of US GAAP regarding financial reporting, presenting the differentiation between the two accounting referential. We note that the accounting information can be the best friend of actual and potential investors if used properly understood.